Optical diagnosis of colorectal polyps with Blue Light Imaging using a new international classification. Issue 2 (1st March 2019) - Subramaniam, Sharmila; Hayee, Bu; Aepli, Patrick; Schoon, Erik; Stefanovic, Milan; Kandiah, Kesavan; Thayalasekaran, Sreedhari; Alkandari, Asma; Bassett, Paul; Coron, Emmanuel; Pech, Oliver; Hassan, Cesare; et al.
Abstract : Background: Blue Light Imaging (BLI) is a new imaging technology that enhances mucosal surface and vessel patterns. A specific BLI classification was recently developed to enable better characterisation of colorectal polyps (BLI Adenoma Serrated International Classification (BASIC)). The aim of this study was to validate the diagnostic performance of BASIC in predicting polyp histology in experienced and trainee endoscopists. Methods: Five experienced and five trainee endoscopists evaluated high‐definition white light (HDWL) and BLI images from 45 small polyps to assess baseline accuracy, sensitivity, specificity, and positive and negative predictive values (NPVs) of polyp histology. Each endoscopist was trained with the BLI classification before repeating the exercise. Results were compared pre‐ and post‐training. Results: The overall pre‐training accuracy improved from 87% to 94%. The sensitivity and NPV of adenoma diagnosis also improved significantly from 79% to 96% and 81% to 95% with BASIC training. This improvement was noted in both groups. The interobserver level of agreement was very good ( K  = 0.90) in the experienced cohort and good ( K  = 0.66) in the trainee group post‐training. Conclusions: BLI is a useful tool for optical diagnosis, and the use of BASIC with adequate training can significantly improve the accuracy, sensitivity and NPV of adenoma diagnosis.